2009
DOI: 10.1111/j.1582-4934.2009.00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Endostatin induces autophagy in endothelial cells by modulating Beclin 1 and β‐catenin levels

Abstract: Endostatin is a well-characterized endogenous inhibitor of angiogenesis that affects cell proliferation and migration by inhibiting integrin and Wnt-mediated signalling pathways. Here, we show that endothelial cells treated with native and P125A-endostatin activate autophagy. Because autophagy can either be protective or induce programmed cell death, experiments were carried out to understand the signalling pathways leading to autophagy in endothelial cells. P125A-endostatin treatment increased the levels of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
91
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 38 publications
4
91
0
2
Order By: Relevance
“…Remarkably, our findings are corroborated by other studies that depict a number of angiostatic matrix proteins and their domains, including endostatin (75) and Kringle V (76), which can concurrently induce autophagy. Notably, a recent study also illustrated that the natural compound capsicodendrin exhibits angiostatic activity and autophagy induction via VEGFR2 inactivation (77).…”
Section: Discussionsupporting
confidence: 80%
“…Remarkably, our findings are corroborated by other studies that depict a number of angiostatic matrix proteins and their domains, including endostatin (75) and Kringle V (76), which can concurrently induce autophagy. Notably, a recent study also illustrated that the natural compound capsicodendrin exhibits angiostatic activity and autophagy induction via VEGFR2 inactivation (77).…”
Section: Discussionsupporting
confidence: 80%
“…Endostatin Induces Autophagy in ECs through IRE1␣-mediated XBP1 mRNA Splicing-Angiogenesis inhibitors, such as endostatin, are reported to induce autophagy in ECs (29). In this study, ECs treated with endostatin induced autophagy, as demonstrated by the appearance of autophagic vacuole structures (Fig.…”
Section: Beclin-1 Deficiency In Ecs Abolishes the Xbp1-inducedmentioning
confidence: 50%
“…However, PEDF-TG and PEDF Ϫ/Ϫ mice bred normally and were overtly healthy, suggesting that there may be functional overlaps between PEDF and other endogenous Wnt inhibitors during development. Previous studies have identified a number of proteins which regulate Wnt signaling through binding to LRP6, including the DKK family, endostatin, and IGFBP4 (47,79,83). Recently, we have shown that another angiogenic factor, SERPINA3K, a member of serine proteinase family which shares 84% sequence homology with PEDF, also binds to LRP6 (78).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have suggested that decreased PEDF levels contribute to inflammation, vascular leakage, and NV in several pathological conditions (27,64). Our recent studies have shown that the Wnt pathway is overactivated in the retina of human patients with DR and in the retina of streptozotocin (STZ)-induced diabetic rats, Akita mice, and OIR rats (18,47). Furthermore, blockage of the Wnt pathway using DKK1 ameliorated retinal inflammation, vascular leakage, and NV in these models, suggesting that dysregulation of the Wnt pathway in diabetes plays a pathogenic role in DR (18).…”
Section: Discussionmentioning
confidence: 99%